al-Muʻjam al-Nabaṭī : dirāsah taḥlīlīyah muqāranah lil-mufradāt wa-al-alfāẓ al-Nabaṭīyah - Dhuyayb, Sulaymān ibn ʻAbd al-Raḥmān (Maṭbūʻāt Maktabat al-Malik Fahd al-Waṭanīyah., 2000)
Nabataean lexicon; comparative studies; dictionaries.